Colds, rheumatism and hysteria… Young women’s ailments and health care in the 19th century in the light of theoretical considerations - Raińska, Kinga (Marginesy, 2021)
People in the first half of the 19th century did not pay much attention to their health. Especially young women did not care for themselves at all or tried to keep healthy in an inappropriate or exaggerated way. This situation, however, began to change over the years and the issue of health improvement and hygiene in the society became a permanent topic of discussion among physicians, hygienists, educators and publicists. The first proposals for women to focus on their hygiene, dress up appropriately and care for their health from the earliest age/years appeared in numerous publications in the 1850s. It was the mother’s duty to care about the health condition, education and upbringing and the recommendations for the improvement in child care quality became one of the elements of the “grassroots work” programme. Texts published in guide literature, very popular at the time, taught women that only good health could allow them to fulfil their life mission: giving birth to healthy children, supporting the husband and keeping an eye on everyday life. New patterns in nutrition, cleanliness, physical fitness and clothing were also promoted.Publications of the 19th century guide literature discussed an entire repertoire of treatments meant to ensure longevity, good health and positive attitude among young women. The majority of these pieces of advice were most likely ignored on a daily basis. By criticizing the inappropriate presence of hygiene in everyday life, the authors of the guidebooks advocated its reforms and recommended making adjustments dictated by time and the development of modern medicine. It is worth mentioning that great emphasis was put on personal hygiene and physical activity, elements which mostly had not been mentioned before. Exercise was meant to improve fitness and serve as a source of energy for the years to come. Order and cleanliness in people’s closest surroundings and following the basic principles of personal hygiene were believed to result not only in good physical health, but in the feeling of mental comfort as well.